A 10 kN portable electromagnetic vibrator for near-surface studies. Issue 1 (1st December 2019) - Dean, Tim; Nguyen, Hoang
Summary: In a previous paper, we described how a small electromagnetic vibrator could be manufactured using commercially available components for less than US$2, 000. The basis of the unit was a set of four low-frequency actuators designed for use in home-theatre systems. In this paper we describe a new unit with the number of actuators increased from four to ten and improved quality electronic components. The maximum output of the vibrator, as measured using load-cells, was more than 10 kN; when operating the unit in the field we noticed that the weight of the vehicle was not sufficient to prevent it decoupling. Variation between the load-cell and accelerometer measurements, consistent with similar studies conducted using hydraulic vibrators, suggests that the new unit has considerable potential as a research tool looking at issues such as baseplate flexure. A VSP acquired using distributed acoustic sensing showed signal to a depth of 850 m for a single sweep.